Rain Water Harvesting : A Compulsory Element for Future Projects - Prasad, Mahesh (AMC Indian Journal of Civil Engineering, 2024)
As the term itself reveals, rain water harvesting aims at two things, first receiving the rainwater properly to store and conserve it, and second to put it to optimum utilization, minimizing wastages. It is a well realized fact that as on date, water remains the most vital requirement for life of human beings, plants as well as animals. Hence, water must be stored properly, conserved for longer duration and utilized judiciously to cut the wastage of water at all stages. A rainwater harvesting system comprises certain components at various stages, the first and foremost is the â€œCatchmentâ€ which can be a small house roof top or it may be large city zone itself from where the entire rain water is desired to be harvested. The other components are a designed system for transporting rainwater which may be a network of pipes / drains leading to storage destination. A filtration system is required to enhance the usefulness of harvested water and finally, a well designed storage in tanks for long term storage of harvested water and also a mechanism to divert the surplus water for recharge of underground aquifers time to time. Use of rain water as drinking water, water for irrigation of crops, water for arboriculture, and forestation purpose has been there since very ancient times, but the use of rain water for recharge of underground aquifers has acquired a bigger dimension in recent times due to fast pace of urbanization and over exploitation of underground water by small and large cities. With increased pace of building constructions, roads and pavements constructions, the land area available for percolation of runoff has been shrinking rapidly. This had an adverse affect on water table all over. The use of water from underground resources has been increasing day by day. The underground aquifers are found to be drying up year by year. This is an alarming signal for human civilization. Hence, rain water harvesting (RWH) particularly, with an aim to recharge the underground aquifers need to have a prime focus of the Government while planning all major urbanization schemes as well as large infrastructure projects.